Association between Heart Rate Variability, Blood Pressure and Autonomic Activity in Cyclic Alternating Pattern during Sleep - Kondo, Hideaki (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: Cyclic alternating pattern (CAP) is frequently followed by changes in heart rate (HR) and blood pressure (BP), but the sequential associations between CAP and autonomic nerve activity have not been studied. The study aimed to reveal the precise changes in heart rate variability (HRV) during phase A of the CAP cycle. DESIGN: Polysomnography was recorded according to the CAP Atlas (Terzano, 2002), and BP and electrocardiogram were simultaneously recorded. The complex demodulation method was used for analysis of HRV and evaluation of autonomic nerve activity. SETTING: Academic sleep laboratory. PARTICIPANTS: Ten healthy males. MEASUREMENTS AND RESULTS: The increase in HR (median [first quartile – third quartile]) for each subtype was as follows: A1, 0.64 (-0.30 to 1.69), A2, 1.44 (0.02 to 3.79), and A3, 6.24 (2.53 to 10.76) bpm (A1 vs. A2 P < 0.001, A1 vs. A3 P < 0.001, A2 vs. A3 P < 0.001). The increase in BP for each subtype was as follows: A1, 1.23 (-2.04 to 5.75), A2, 1.76 (-1.46 to 9.32), and A3, 12.51 (4.75 to 19.94) mm Hg (A1 vs. A2 P = 0.249, A1 vs. A3 P < 0.001, A2 vs. A3 P < 0.001). In all of phase A, the peak values for HR and BP appeared at 4.2 (3.5 to 5.4) and 8.4 (7.0 to 10.3) seconds, respectively, after the onset of phase A. The area under the curve for low-frequency and high-frequency amplitude significantly increased after the onset of CAP phase A (P < 0.001) and was higher in the order of subtype A3, A2, and A1 (P < 0.001). CONCLUSIONS: All phase A subtypes were accompanied with increased heart rate variability, and the largest heart rate variability was seen in subtype A3, while a tendency for less heart rate variability was seen in subtype A1. CITATION: Kondo H; Ozone M; Ohki N; Sagawa Y; Yamamichi K; Fukuju M; Yoshida T; Nishi C; Kawasaki; Mori; Kanbayashi T; Izumi M; Hishikawa Y; Nishino S; Shimizu T. Association between heart rate variability, blood pressure and autonomic activity in cyclic alternating pattern during sleep. SLEEP 2014;37(1):187-194.